2001
DOI: 10.1093/emboj/20.1.222
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Epstein-Barr virus-based plasmid partitioning in budding yeast

Abstract: The EBNA1 protein of Epstein±Barr virus (EBV) mediates the partitioning of EBV episomes and EBVbased plasmids during cell division by a mechanism that appears to involve binding to the cellular EBP2 protein on human chromosomes. We have investigated the ability of EBNA1 and the EBV segregation element (FR) to mediate plasmid partitioning in Saccharomyces cerevisiae. EBNA1 expression alone did not enable the stable segregation of FR-containing plasmids in yeast, but segregation was rescued by human EBP2. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 60 publications
4
83
0
Order By: Relevance
“…However, although EBNA1 is unlikely to interact with cognate cell DNA to affect cell gene expression or growth, we cannot dismiss the possibility that EBNA1 may interact with cell proteins and affect cells through pathways that may not have been detectable in the experiments described here. EBNA1 N-terminal residues have been implicated in interaction with the cellular proteins p32 and EBP2, and interaction with EBP2 is important in episome persistence (48,49). Also, EBNA1 amino acids 91-321 are a glycine-alanine repeat domain that can inhibit proteasome-mediated degradation of EBNA1 (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, although EBNA1 is unlikely to interact with cognate cell DNA to affect cell gene expression or growth, we cannot dismiss the possibility that EBNA1 may interact with cell proteins and affect cells through pathways that may not have been detectable in the experiments described here. EBNA1 N-terminal residues have been implicated in interaction with the cellular proteins p32 and EBP2, and interaction with EBP2 is important in episome persistence (48,49). Also, EBNA1 amino acids 91-321 are a glycine-alanine repeat domain that can inhibit proteasome-mediated degradation of EBNA1 (20).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the novel 2m CUTs function to regulate the expression of their respective antisense mRNAs in a manner similar to that suggested for GYP5 and its antisense RNA ). Humans contain a single apparent Air protein homolog, ZCCHC7, and segregation of Epstein-Barr virus episomes appears to follow similar rules to that of the yeast 2m plasmid (Kapoor et al 2001;Kapoor and Frappier 2003). Thus it is tempting to speculate that a similar mechanism may govern the inheritance of yeast plasmids and viral genomes in metazoans.…”
Section: à30mentioning
confidence: 99%
“…This protein was discovered as an EBNA1 binding partner in a two-hybrid screen, and residues 325-376 of EBNA1 are important for this interaction (Shire et al, 1999). It was subsequently shown that EBP2 enables EBNA1 to segregate FR-containing plasmids in yeast by facilitating the interaction of EBNA1 with yeast mitotic chromatin (Kapoor and Frappier, 2003;Kapoor et al, 2001). In keeping with this finding, EBP2 associates with human metaphase chromosomes, and silencing of EBP2 expression results in a large decrease in the amount of EBNA1 associated with metaphase chromosomes (Kapoor et al, 2005;Wu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%